Banking information resource cybersecurity system modeling - Olha Shulha; Iryna Yanenkova; Mykhailo Kuzub; Iskandar Muda; Viktor Nazarenko (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The rapid development of the process of informatization of modern society has necessitated cybersecurity in all spheres of human activity, as the implementation of deliberate or unintentional influences on the information sphere by both external and internal sources can damage security and lead to moral, material, financial, reputational and other forms of damage. The purpose of the paper is to create functional cognitive models to assess the level of their protection. The method of building a fuzzy cognitive map of the state of cybersecurity of banks is used. There have been developed cognitive models to determine the level of protection of the computer network, information security system and critical infrastructure (banks). Scenarios have been developed that reflect the response of the system at the complex maximum attenuation of the impact of the most important cyber threats. In conclusion, the practical implementation of the method provides an opportunity to predict the state of cybersecurity of banks, and contributes to the implementation of the necessary mechanisms to prevent, protect and control access at the appropriate levels of network infrastructure.
Keywords: 650; banking information resources; cyber threat; efficiency; hybrid threat; Internet banking